2020
DOI: 10.1038/s41598-020-73919-y
|View full text |Cite
|
Sign up to set email alerts
|

Improved classification of rheumatoid arthritis with a score including anti-acetylated ornithine antibodies

Abstract: The presence of rheumatoid factor (RF) or anti-cyclic citrullinated peptide (anti-CCP) autoantibodies contributes to the current rheumatoid arthritis (RA) classification criteria. These criteria involve stratification on antibody levels, which limits reproducibility, and underperform in the RA patients without RF and anti-CCP. Here, we have explored if two anti-acetylated peptide antibodies (AAPA), anti-acetylated lysine (AcLys) and anti-acetylated ornithine (AcOrn), could improve the performance of the curren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 44 publications
1
10
1
Order By: Relevance
“…Even without the least specific peptide, ac-lysine.inv, the prevalence of AAPA still would be close to 50%. In eRA, the prevalence of individual AAPA ranged from 32% to 39%, which, for ac-lysine, was in reasonable agreement with data from two previous studies, 18 , 33 taking into account that the definition of cut-offs for positivity differed between the three studies. A very recent publication by Rodriguez-Martínez et al demonstrated the value of ac-ornithine implemented in the American College of Rheumatology/ European League Against Rheumatism (ACR/EULAR) classification criteria for RA.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Even without the least specific peptide, ac-lysine.inv, the prevalence of AAPA still would be close to 50%. In eRA, the prevalence of individual AAPA ranged from 32% to 39%, which, for ac-lysine, was in reasonable agreement with data from two previous studies, 18 , 33 taking into account that the definition of cut-offs for positivity differed between the three studies. A very recent publication by Rodriguez-Martínez et al demonstrated the value of ac-ornithine implemented in the American College of Rheumatology/ European League Against Rheumatism (ACR/EULAR) classification criteria for RA.…”
Section: Discussionsupporting
confidence: 89%
“… 6 Their data on sensitivity and specificity of AAPA are in good agreement with our results. However, in this study, a high prevalence of AAPA in RF/ACPA negative patients could not be shown, because only ac-lysine and ac-ornithine antibodies were determined, 33 while we found ac-lysine.inv to be the most common antibody in RF/ACPA-negative eRA. Furthermore, in the study of Rodriguez-Martínez et al ., different cut-offs were used for the two assays, whereas we decided to use uniform cut-offs for all three assays, which increased the overall sensitivity of AAPA testing.…”
Section: Discussioncontrasting
confidence: 74%
See 2 more Smart Citations
“…Other well established autoantibodies against PTMs also show potential value as biomarkers. For example, the presence of anti-carbamylated protein antibodies or anti-acetylated peptide antibodies can be used to improve RA disease classification [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%